An Optimized Topology Discovery Mechanism in Software Defined Networks - LI Lan-ying; WANG Min; ZHU Su-xia (Journal of Harbin University of Science and Technology)
Aiming at the problems of excessive resource consumption and low operating efficiency in the topology discovery mechanism in Software Defined Networks (SDN), a stronger topology discovery mechanism (S-OFDP) is proposed. First, based on the idea of minimum vertex coverage of the graph, the greedy algorithm is used to achieve the minimum switch coverage of the network topology, and then the port classification and hash strategy are used to eliminate redundant data packets in the network. The simulation results show that compared with the existing topology discovery mechanism, the efficiency gain of the total LLDP in the network under S-OFDP can reach 48.66%. Therefore, S-OFDP can effectively reduce the number of LLDP in the network, so as to reduce resource consumption and reduce the load of the controller.